2014
DOI: 10.1007/s10549-014-3086-4
|View full text |Cite|
|
Sign up to set email alerts
|

Vaccination with ErbB-2 peptides prevents cancer stem cell expansion and suppresses the development of spontaneous tumors in MMTV-PyMT transgenic mice

Abstract: ErbB-2 has been implicated as a target for cancer-initiating cells in breast and other cancers. ErbB-2-directed peptide vaccines have been shown to be effective in prevention of spontaneous tumorigenesis of breast in neu transgenic mouse model, and cellular immunity is proposed as a mechanism for the anti-tumor efficacy. However, there has been no explanation as to how immunity suppresses tumorigenesis from the early stage carcinogenesis, when ErbB-2 expression in breast is low. Here, we investigated a peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In addition, the neutralization of IFN-γ, HMGB1 or interferon (α, β and Ω) receptor 1 (IFNAR1), as well as the knockout of myeloid differentiation primary response gene 88 (Myd88), which encodes a signal transducer operating downstream of many Toll-like receptors, abrogates the therapeutic efficacy of anti-ERBB2 mAbs in mouse models of BC 103,104 , indicating that trastuzumab may also promote ICD. In fact, preclinical data suggest that the induction of CTL-dependent immune responses against ERBB2 might constitute a valuable therapeutic goal 105 . A phase 1/2 clinical study concluded that the HLA-A2 + BC patients immunized with a peptide derived from ERBB2 and granulocyte-macrophage colony-stimulating-factor (GM-CSF) exhibit an improved 5-year disease-free survival as compared to HLA-A2 -patients treated with GM-CSF only 106 .…”
Section: Type I Interferonsmentioning
confidence: 99%
“…In addition, the neutralization of IFN-γ, HMGB1 or interferon (α, β and Ω) receptor 1 (IFNAR1), as well as the knockout of myeloid differentiation primary response gene 88 (Myd88), which encodes a signal transducer operating downstream of many Toll-like receptors, abrogates the therapeutic efficacy of anti-ERBB2 mAbs in mouse models of BC 103,104 , indicating that trastuzumab may also promote ICD. In fact, preclinical data suggest that the induction of CTL-dependent immune responses against ERBB2 might constitute a valuable therapeutic goal 105 . A phase 1/2 clinical study concluded that the HLA-A2 + BC patients immunized with a peptide derived from ERBB2 and granulocyte-macrophage colony-stimulating-factor (GM-CSF) exhibit an improved 5-year disease-free survival as compared to HLA-A2 -patients treated with GM-CSF only 106 .…”
Section: Type I Interferonsmentioning
confidence: 99%
“…Moreover, for dataset GSE10797 in a four-class case, we also found some evidence with the help of KEGG pathway search, we found that several pathways are statistically significant, e.g., hsadd05200 Pathways in cancer, hsa04012 ErbB signaling pathway and hsadd04510 Focal adhesion pathway. ErbB-2 is a target for cancer-initiating cells in breast and other cancers [ 28 ]. Amplification and subsequent overexpression of the HER2 encoding oncogene results in unregulated cell proliferation in HER2-positive breast cancer [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sphere‐forming GBM stem cells showed higher susceptibility to CTL than did NK cells . HER2‐specific peptide vaccination decreased aldehyde dehydrogenase (ALDH)‐positive breast cancer stem cells in MMTV‐PyMT transgenic breast cancer model mice . All of these observations in humans and mice suggest that treatment‐resistant CSC/CIC are sensitive to differentiated CTL both in vitro and in vivo .…”
Section: Immunological Phenotypes Of Cancer Stem‐like Cellsmentioning
confidence: 99%